The herbicides glyphosate and glufosinate and the cyanotoxin β-N-methylamino-l-alanine induce long-term motor disorders following postnatal exposure: the importance of prior asymptomatic maternal inflammatory sensitization - Oummadi, Asma; Menuet, Arnaud; Méresse, Sarah; Laugeray, Anthony; Guillemin, Gilles; Mortaud, Stéphane (Frontiers in Neuroscience, 2023)
Background: Prenatal Maternal Immune Activation (MIA) and/or perinatal exposure to various xenobiotics have been identified as risk factors for neurological disorders, including neurodegenerative diseases Epidemiological data suggest an association between early multi-exposures to various insults and neuropathologies. The“Multiple-hit Hypothesis” assumes that prenatal inflammation makes the brain more susceptible to subsequent exposure to several kind of neurotoxins. To explore this hypothesis and its pathological consequences, a behavioral longitudinal procedure was performed after a prenatal sensitization and postnatal exposure to low dose of pollutants. Methods: A maternal exposure to an acute immune challenge (first hit) was induced by an asymptomatic LPS dose (0,008 mg/kg) in mice. This sensitization was followed by exposing the offspring to environmental chemicals (second hit) postnatally, by oral route. The chemicals used were low doses of the cyanotoxin β-N-Methylamino-L-Alanine (BMAA; 50 mg/kg), the herbicide Glufosinate Ammonium (GLA; 0,2 mg/kg) or the pesticide Glyphosate (GLY; 5 mg/kg). After assessing maternal parameters, a longitudinal behavioral was carried out on offspring in order to evaluate motor and emotional abilities at adolescence and adulthood. Results: We finally showed that the low LPS immune challenge was an asymptomatic MIA. Even though a significant increase in systemic pro-inflammatory cytokines was detected in the dams, no maternal behavioural defects were observed. In addition, as shown by rotarod assays and openfield device, this prenatal LPS administration alone did not show any behavioral disruption in offspring. Interestingly, our data showed that offspring subjected to both MIA and post-natal BMAA or GLA exposure displayed motor and anxiety behavioral impairments during adolescence and adulthood. However, this synergistic effect was not observed in GLY exposed offsprings. Conclusion: These data demonstrated that prenatal and asymptomatic immune sensitization represent a priming effect to subsequent exposure to low doses of pollutants. This double-hits act in synergy to induce motor neurons disease related phenotypes in offspring. Thus, our data strongly emphasize that multiple exposures for developmental neurotoxicity regulatory assessment must be considered. This work paves the way for future studies aiming at deciphering cellular pathways involved in these sensitization processes.